Cholinergic signalling in the forebrain controls microglial phenotype and responses to systemic inflammation - Cunningham, Colm (My University, 2021)
Loss of basal forebrain cholinergic projections occurs in Alzheimer’s disease, frontotemporal dementia and in aging. Moreover, nicotinic stimulation is anti-inflammatory in macrophages and microglia but how loss of basal forebrain acetylcholine impacts on microglial phenotype is poorly understood. Here we hypothesized that endogenous ACh maintains homeostatic microglial phenotype and that neurodegeneration-evoked loss of ACh tone, triggers microglial activation. Using the specific immunotoxin, mu-p75NTR-saporin, we performed partial lesions of the basal forebrain cholinergic nuclei, medial septum and ventral diagonal band. We examined microglial phenotype in the hippocampus, the major projection area for these nuclei, using bulk RNA preparations, Flow cytometry-sorted microglial cells, immunohistochemistry and ELISA to examine responses to cholinergic withdrawal and acute responses to subsequent systemic inflammation with LPS. Basal forebrain cholinergic degeneration elicited lasting activation of microglia in the hippocampus, showing suppression of Sall1 and persistent elevation of Trem2, Clec7a, Itgax and complement genes proportionate to Chat loss. These primed microglia showed exaggerated IL-1β responses to systemic LPS challenge. In normal animals LPS evoked acute increases in extracellular choline, a proxy for ACh release, and this response was lost in lesioned animals. Restoration of basal cholinergic signalling via serial treatments with the nicotinic agonist PNU282,987 resulted in reversion to the homeostatic microglial phenotype and prevented exaggerated responses to acute systemic inflammation. The data indicate that neurodegeneration-evoked loss of cholinergic tone, triggers microglial activation via impaired microglial nicotinic signalling and leaves these microglia more vulnerable to secondary inflammatory insults. The data have implications for neuroinflammation during aging and neurodegeneration and for responses to sepsis and systemic inflammation.
PUBLISHED
Keywords: Acetylcholine; microglia; priming; delirium; sepsis; neuroinflammation; BASAL FOREBRAIN; BIOLOGY; CHOLINERGIC; ENDOCRINOLOGY; IMMUNOLOGY; INFLAMMATION; Internal Medicine; MEDICINE; MICROGLIA; NEURODEGENERATION; Neuroscience